A new antifungal macrolide from Streptomyces sp. KIB-H869 and structure revision of halichomycin. Issue 12 (23rd March 2016) - Yu, Zhiyin; Wang, Li; Yang, Jing; Zhang, Fan; Sun, Yun; Yu, Mingming; Yan, Yijun; Ma, Ya-Tuan; Huang, Sheng-Xiong
Graphical abstract: Abstract: A new hygrolidin-type macrolide (1 ), together with one known derivative, oxohygrolidin (2 ), were isolated from the culture of Streptomyces sp. KIB-H869. The structure of the new compound was elucidated by means of extensive spectroscopic analysis. Moreover, by the biogenesis ratiocination and NMR data comparison, halichomycin and2 were confirmed to have the same structure, which corrects the structural misrepresentation of halichomycin. The antifungal activities of the two compounds were evaluated.